2019
DOI: 10.3899/jrheum.181093
|View full text |Cite
|
Sign up to set email alerts
|

The OMERACT MRI in Enthesitis Initiative: Definitions of Key Pathologies, Suggested MRI Sequences, and a Novel Heel Enthesitis Scoring System

Abstract: Objective.To develop and validate an enthesitis magnetic resonance imaging (MRI) scoring system for spondyloarthritis/psoriatic arthritis, using the heel as model.Methods.Consensus definitions of key pathologies and 3 heel enthesitis multireader scoring exercises were done, separated by discussion, training, and calibration.Results.Definitions for bone and soft tissue pathologies were agreed. In the final exercise, median pairwise single-measures intraclass correlation coefficients (ICC; patient-level) for ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 14 publications
0
37
0
1
Order By: Relevance
“…Therefore, inflammatory changes of pulleys could also be appropriate for the evaluation of disease-driven joint involvement [24]. In early 2019, Mathew et al introduced a preliminary enthesitis-based MRI scoring system, named "Heel Enthesitis Scoring System" (HEMRIS) that emphasizes the value of entheseal changes for the diagnosis and monitoring of PsA [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inflammatory changes of pulleys could also be appropriate for the evaluation of disease-driven joint involvement [24]. In early 2019, Mathew et al introduced a preliminary enthesitis-based MRI scoring system, named "Heel Enthesitis Scoring System" (HEMRIS) that emphasizes the value of entheseal changes for the diagnosis and monitoring of PsA [26].…”
Section: Discussionmentioning
confidence: 99%
“…The Outcome Measures for Rheumatoid Arthritis Clinical Trials (OMERACT) working group has developed a semi-quantitative PsA MRI (sum-)score (PsAMRIS) that is highly sensitive for disease-related joint changes and is widely used for therapy monitoring [22][23][24]. However, until most recently, enthesitis was not included in any MRI score, despite being a hallmark of PsA [25,26]. Indeed, enthesitis is difficult to accurately evaluate in small joints using conventional MRI or with high-resolution MRI surface coils that can only visualize a small area.…”
Section: Introductionmentioning
confidence: 99%
“…The recently published OMERACT heel enthesitis scoring system (HEMRIS) is a promising scoring system for trained MRI readers [12]. HEMRIS includes in ammatory ndings and structural MRI ndings for the assessment of heel enthesitis, and the nal score depends on a consensus-based approach of MR images by the investigators.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggested a need for reliable and validated MRI scoring system for enthesitis. Subsequently, The OMERACT MRI group developed consensus definitions of key pathologies and three heel enthesitis multi-reader scoring exercises were done, separated by discussion, training and calibration [4]. In a final exercise, median pairwise single-measures intra-class correlation coefficients (ICCs; patient-level) for entheseal inflammation status/change scores were 0.83/0.82 for all readers.…”
Section: Referencesmentioning
confidence: 99%
“…For radiologists and selected rheumatologists ICCs were 0.91/0.84 and quadratic-weighted kappas (lesion-level) 0.57-0.91/0.45-0.81. It was concluded that the proposed definitions and heel enthesitis scoring system (OMER-ACT HEMRIS) are reliable among trained readers and promising for clinical trials [4]. This talk will briefly review the evidence behind the use of MRI for diagnosis and monitoring enthesitis, describe the recently developed OMERACT consensus definitions of key pathologies, and provide examples of these pathologies, aiming for the attendees to learn to be able to recognize them.…”
Section: Referencesmentioning
confidence: 99%